THE CALCULATION TECHNIQUE FOR TRANSPORT OF SNOW IN POORLY-STUDIED AREAS (SAKHALIN ISLAND) - V. A. Lobkina; E. N. Kazakova; Yu. V. Gensiorovsky (Лëд и снег, 2015)
Wind spatial redistribution of snow influences on exploitation of linear constructions; it is one of the principal factors of snow cornice’s forming on slopes. Calculation of snow-drift transport is indispensable when solving of practical problems. There are not enough actual data on snowstorm’s characteristics for many regions ofRussia, so we should use substituted data when we calculate the volume of snow-drift transport. Currently, the snow-drift observations are not carrying out on the network of hydrometeorological stations. There are several methods to calculate volume of snow-drift transport using only data of hydrometeorological stations (methods of D.M. Melnik, A.K. Dyunin and others). In this paper, we calculated the intensity and volume of snow-drift transport for two parts of west coast of SouthSakhalinusing different methods. And we should conclude that there is necessity to improve snow drifting research having the aim to solve practical problems.